(untitled) (Estudios humanísticos. Geografía, historia y arte, 1994)
The choir of the cathedral of León, originally placed in the bays before the main altar, had several attempts of removal since the XVI century, because of his inconvenient position to follow the sacred services. The move was finally made in the first half of XVIII century, when the choir was established in the first bay of the central nave of the church, where it remains nowadays.